2010
DOI: 10.1002/edn.160
|View full text |Cite
|
Sign up to set email alerts
|

Self-management interventions for type 2 diabetes: a systematic review

Abstract: FTIR spectroscopy and thermal analysis were applied to study the nylon 6–lithium salt systems. The DTA results show that lithium ions cause a significant reduction of the melting point of nylon–lithium salt samples. In addition, lithium salts can also prevent the crystallization of molten nylon in the cooling process. Temperature‐variable FTIR spectroscopy demonstrates that stronger hydrogen bonds form when nylon–lithium halide is molten. Such stronger hydrogen bonds in molten nylon lithium systems may account… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
99
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(114 citation statements)
references
References 36 publications
5
99
0
4
Order By: Relevance
“…We identified 14,841 references for screening, of which 17 were included in this meta-review [99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114][115] ( Figure 10). A total of 322 RCTs were included within these 17 systematic reviews.…”
Section: Systematic Reviews Identifiedmentioning
confidence: 99%
See 3 more Smart Citations
“…We identified 14,841 references for screening, of which 17 were included in this meta-review [99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114][115] ( Figure 10). A total of 322 RCTs were included within these 17 systematic reviews.…”
Section: Systematic Reviews Identifiedmentioning
confidence: 99%
“…100,101,104,106,109,110,112,114,115 The four most commonly reported self-management behaviours were diet, physical activity (PA), self-monitoring of blood glucose (SMBG) and foot care behaviours. Three reviews found strong evidence to support the role of self-management interventions in facilitating dietary change.…”
Section: Secondary Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple studies confirm the value of diabetes selfmanagement education, demonstrating improved clinical outcomes, quality of life and healthy coping, increased use of primary and preventive services and reductions in diabetes-related costs [3][4][5][6]. Despite the evidence for the effectiveness of diabetes self-management education, participation rates were low for both patient and family groups in DAWN2.…”
mentioning
confidence: 99%